2004
DOI: 10.1007/s00204-004-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of adducts between serum albumin and 4,4?-methylenediphenyl diisocyanate (MDI) in human plasma

Abstract: Diisocyanates are potent inducers of airways disease. Methylenediphenyl diisocyanate (MDI) is a widely used diisocyanate in the chemical industry. The aim of this study was to identify major and also immunologically relevant protein conjugates of MDI in plasma. Plasma was obtained from an MDI-exposed worker. The plasma was dialysed and then fractionated using ion exchange chromatography (IEC) and gel filtration. These fractions and also aliquots of unfractioned plasma were hydrolysed, derivatised and analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…It was also shown in vitro that MDI-specific IgG antibodies are selectively bound to the MDI protein conjugates (Johannesson et al 2004). The HSA adducts are considered to be the primary inductors of T cell-dependent B-lymphocyte stimulation (see Documentation 2000).…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 99%
“…It was also shown in vitro that MDI-specific IgG antibodies are selectively bound to the MDI protein conjugates (Johannesson et al 2004). The HSA adducts are considered to be the primary inductors of T cell-dependent B-lymphocyte stimulation (see Documentation 2000).…”
Section: Metabolism and Toxicokineticsmentioning
confidence: 99%
“…Around 95% of the total MDI adducts in human plasma are albumin adducts (Johannesson et al 2004;Sennbro et al 2003). A 70-kDa protein adduct was found as the main product in the blood of rats after 4-hour inhalation of 14 C-MDI (0.06 and 0.4 mg/m 3 ) (Brown et al 1994).…”
Section: Protein Adductsmentioning
confidence: 99%
“…In the blood it has been shown that the diisocyanates are mainly bound to serum albumin (Lind et al 1997a;Johannesson et al 2004) and the half-life of the adducts in plasma has been reported to be 21 days which is similar to that of albumin (Lind et al 1997b). The adducts will be excreted in urine as low-molecular weight conjugates (Lind et al 1996) when the proteins are degraded.…”
Section: Introductionmentioning
confidence: 98%